Computer Stabilometer Data on State of Postural Functions in Patients with Parkinson's Disease - Poverennova I.E.; Tretiakova N.A. (Саратовский научно-медицинский журнал, 2011)
Postural abnormalities are clinical syndromes that lead to disability in patients with Parkinson's disease. The aim of the study is to investigate the characteristics of postural control in different clinical forms of Parkinson's disease using a computer stabilometer examination. Materials and Methods: Clinical and neurophysiological analysis has been performed in 148 patients with Parkinson's disease who have been divided into groups with akineticorigid, shaking-rigid and shaking forms of the disease. All patients have experienced static stabilometer examination with medical-diagnostic complex «MBN-Biomechanics» (Scientific-Medical Firm MBN, Moscow). Results of the research have proved a significant decrease of compensatory abilities of balance maintenance and the basic standing without dependence on the clinical form of disease. It has been noted that a number of indices have been increased. It has been revealed, that the tremor at rest has influenced significantly the values of such indices. Dissociation between the clinical severity of postural instability and stabilometer indicators reflecting the state of the vertical balance of the body has been revealed. The study has confirmed the importance of the differentiated approach to stabilometer analysis in patients with different forms of Parkinson's disease. Conclusion: Computer stabilometry makes possible the detection of disturbances in postural functions and estimation of their condition in dynamics